Speculation and the Term Structure of Interest Rates - Barillas, Francisco; Nimark, Kristoffer P. (Review of Financial Studies, 2017)
We develop and estimate a tractable equilibrium term structure model populated with rational but heterogeneously informed traders that take on speculative positions to exploit what they perceive to be inaccurate market expectations about future bond prices. The speculative motive is an important driver of trading volume. Yield dynamics due to speculation are (1) statistically distinct from classical term structure components due to risk premiums and expectations about future short rates and are orthogonal to public information available to traders in real time and (2) quantitatively important, accounting for a substantial fraction of the variation of long maturity U.S. bond yields. Received May 12, 2014; editorial decision May 10, 2016 by Editor Pietro Veronesi.